2014
DOI: 10.1002/qua.24838
|View full text |Cite
|
Sign up to set email alerts
|

The quantum dynamics of the reactions N+H2(HD,D2) and their vibrational excitation effect

Abstract: The N( 4 S)1H 2 reaction and its isotopic variants have been investigated by means of time-dependent quantum wave packet with split operator method on the ground state 1 4 A 00 potential energy surface (Zhai and Han, J. Chem. Phys. 2011, 135, 104314). The reaction probabilities, integral cross sections, branching ratio of the integral cross sections, and effect of vibrational excitation of H 2 , HD, and D 2 diatomic molecules are presented and discussed. The results reveal that the intramolecular isotopic eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Study on S( 3 P) + HD verified that the CS approximation is effective for the direct abstraction reaction. Very recent study on N + H 2 (HD,D 2 ) demonstrated that the cheaper CS approximation has done well for this reactive system. In the wave packet calculations on the nonadiabatic O( 3 P) + HF reaction with direct and rather fast dynamics, the CS approximation showed a good agreement with the CC calculation in computing both the total and the state‐to‐state integral cross sections.…”
Section: Introductionmentioning
confidence: 85%
“…Study on S( 3 P) + HD verified that the CS approximation is effective for the direct abstraction reaction. Very recent study on N + H 2 (HD,D 2 ) demonstrated that the cheaper CS approximation has done well for this reactive system. In the wave packet calculations on the nonadiabatic O( 3 P) + HF reaction with direct and rather fast dynamics, the CS approximation showed a good agreement with the CC calculation in computing both the total and the state‐to‐state integral cross sections.…”
Section: Introductionmentioning
confidence: 85%
“…[22,23] Due to the abundance of D (deuterium) in nature, a great deal of research related to the isotopic reaction systems has been done, which revealed some pronounced isotope effects on the scalar and vector properties of certain elementary reactions. [24][25][26][27] To the best of our knowledge, little research has been done in O( 3 P) + H + 2 → OH + + H and → OH + H + isotopic reactions. In this study, we carry out the QCT calculations to investigate the isotope effects of these reactions.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the properties of the C( 1 D) + H 2 and its isotopic variants seem with the features of an insertion mechanism. Zhang et al [12] investigated the N + H 2 reaction and its isotopic variants through the time-dependent quantum wave packet method with the split operator scheme. In their work, the reaction probabilities, ICSs, branching ratio of the ICSs, and vibrational excitation effect of H 2 , HD, and D 2 diatomic molecules were calculated.…”
Section: Introductionmentioning
confidence: 99%